2016
DOI: 10.1016/j.celrep.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Reporter Mouse for Inflammasome Assembly Demonstrates an Important Role for Cell-Bound and Free ASC Specks during In Vivo Infection

Abstract: Summary Inflammasome activation is associated with numerous diseases. However, in vivo detection of the activated inflammasome complex has been limited by a dearth of tools. We developed transgenic mice that ectopically express the fluorescent adaptor protein, ASC (apoptosis-associated speck-like protein containing a caspase recruitment domain), and characterized the formation of assembled inflammasome complexes (“specks”) in primary cells and tissues. In addition to hematopoietic cells, we found that a stroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
115
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 34 publications
5
115
0
Order By: Relevance
“…Extracellular ASC specks were detected in tissues from patients and mice with chronic respiratory diseases, or systemically in the sera of patients with autoinflammatory diseases . These findings consolidate several earlier speculations, and extracellular ASC specks have now been observed in different studies, in vitro and in vivo . ASC specks were shown to be released by inflammasome‐activated macrophages and associated with ectopically delivered POP1, which prevented their inflammatory properties in recipient cells, or after their injection into mice .…”
Section: Extracellular Asc Specks—mechanisms Of Release and Uptakesupporting
confidence: 79%
See 2 more Smart Citations
“…Extracellular ASC specks were detected in tissues from patients and mice with chronic respiratory diseases, or systemically in the sera of patients with autoinflammatory diseases . These findings consolidate several earlier speculations, and extracellular ASC specks have now been observed in different studies, in vitro and in vivo . ASC specks were shown to be released by inflammasome‐activated macrophages and associated with ectopically delivered POP1, which prevented their inflammatory properties in recipient cells, or after their injection into mice .…”
Section: Extracellular Asc Specks—mechanisms Of Release and Uptakesupporting
confidence: 79%
“…ASC specks were shown to be released by inflammasome‐activated macrophages and associated with ectopically delivered POP1, which prevented their inflammatory properties in recipient cells, or after their injection into mice . In two independent studies, mice expressing a fluorescent ASC‐reporter construct revealed the release of ASC specks into the extracellular space and their accumulation in tissues upon challenge with inflammasome activators, bacterial, or viral infection . More recently, a study describing the generation of a Zebrafish ASC‐reporter model confirmed the release of ASC specks by keratinocytes, and showed their uptake by surrounding immune cells .…”
Section: Extracellular Asc Specks—mechanisms Of Release and Uptakementioning
confidence: 95%
See 1 more Smart Citation
“…In lung fibroblasts, caspase-1-dependent IL-1β secretion occurs independently of NLRP3 suggesting cell type-specific functions of NLRP3 in inflammasome activation (Ichinohe et al, 2009). Formation of ASC specks was also shown in tissue sections and lung fibroblasts from mice expressing fluorescent ASC protein further demonstrating inflammasome activity in non-hematopoietic cells (Tzeng et al, 2016). ASC speck formation was observed mainly in cells that stained positive for influenza virus nucleoprotein suggesting that inflammasome assembly occurs primarily in cells infected with influenza virus (Tzeng et al, 2016).…”
Section: Activation Of Nlrp3 Inflammasome During Influenza Virus Imentioning
confidence: 89%
“…Detection of ASC specks in mouse primary cells will be simplified by reporter mice that express fluorescent fusions of ASC (Tzeng et al . ). Once inflammasome assembly has been observed, the involved inflammasome sensor could be detected by PLAs using antibodies or nanobodies against ASC as well as individual candidate sensors.…”
Section: Inflammasomesmentioning
confidence: 97%